Taxonomic notes on the species of the genus Anterhynchium de Saussure, 1863 (Hymenoptera: Vespidae: Eumeninae) from Vietnam, with description of a new species - Nguyen, Lien Thi Phuong (Zootaxa, 2015)
A taxonomic study on the solitary wasps in the vespid genus Anterhynchium de Saussure, 1863, from Vietnam is presented. One species previously identified as A. (Anterhynchium) abdominale abdominale (Illiger, 1802) is described as new, namely A. punctatum Nguyen, sp. nov. Antechynchium (Dirhynchium) flavolineatum flavolineatum (Smith, 1857) and A. (Dirhynchium) flavomarginatum flavomarginatum (Smith, 1852) are newly recorded from Vietnam. New synonymy is proposed for A. flavolineatum flavolineatum (Smith, 1857) =A. flavolineatum malaisei van der Vecht, 1963, syn. nov. A. coracinum van der Vecht sensu Girish Kumar (2013) is a misidentification of A. f. flavomarginatum (Smith), and the record of this species from Pakistan and India belongs to A. f. flavolineatum. A key to species of the genus from Vietnam is provided.